Mindfulness and Self-Compassion Based Interventions for Substance Use Disorders: A Literature Review - Platt, Keith Allen (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This literature review examines eight peer reviewed studies reporting on the efficacy of mindfulness-based and self-compassion-based interventions for adults diagnosed with substance use disorders. Prevalence of substance use disorders is provided, and relevant definitions are discussed. The syndrome model of addiction is advanced as an etiological explanation, and the search methodology described. Results of this literature review support mindfulness training as an effective intervention for substance use disorders. Only one study supporting self-compassion as an effective intervention for substance use disorders was reviewed so it is not possible at this time to make a judgment regarding the efficacy of that intervention. Limitations of this body of literature include attrition, unmatched treatment conditions, and lack of fidelity measures. Recommendations include more self-compassion research, more use of fidelity scales in intervention research, and greater use of mindfulness-based interventions in substance use disorder treatment.